Assessment of Physicochemical, Hygiene Performance and Bacteriological Quality of Stored Water in Selected Hostels in Malete, Kwara State, Nigeria - Abimbola Jimoh, Fausat; Taiwo Ajao, Abdullahi; Wakili , Tope Aborisade; Abdulsalam, Zainab Biola; Olanrewaju , Sariyat Olayinka (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2025)
Water quality assessment is crucial in ensuring the safety and health of individuals, especially in residential areas like student hostels. This study assessed the physicochemical parameters, hygiene performance, and bacteriological quality of stored water in hostels in Malete, Nigeria. Twenty different water samples were collected and analyzed for key physicochemical properties and hygiene practices related to water storage and handling. Membrane filtration technique was employed for the bacteriological estimation and identification of the isolates were carried out using standard methods. Hygiene performance indices ranged from 40- 80 % of the stored water samples. The findings revealed varying levels of physicochemical properties; Temperature oscillated from (26.0- 28.4 °C), TDS (48.0– 690.0 mg/L), pH (5.44-7.61), EC in µS/cm (96.0 689.0), salinity (0.0-0.01%) and resistivity (1.170– 4.910 MΩ/cm). Total Bacterial Count ranged from 80.0 ±0.5.77- 200±20.0 CFU/100ml, Total Coliform Count (0.0- 100±10.00 CFU/100ml), Total Faecal Coliform Count (0.0– 10.0±0.0 CFU/100ml), Total Salmonella- Shigella (0.0 100±26.45 CFU/100ml) and Total Pseudomonad Count (0.0- 100±20.00 CFU/100ml). Poor hygiene practices, such as inadequate container cleaning and direct hand contact, contributed to bacterial contamination. The presence of coliforms in almost all the samples indicated potential health risks. This study highlights the need for improved water management practices and regular monitoring to ensure safe drinking water for hostel residents in Malete, Kwara State. Implementing proper hygiene education and water treatment methods is recommended.